Beginner's Guide to Go Protocol Buffer. - Moses, Martine (linkedin.com, 2023)
Get a practical, hands-on introduction to creating lightning-fast APIs using the Google Protocol Buffer (protobuf) and Google Remote Procedure Call (gRPC).